Robotic technology in total knee arthroplasty: a systematic review. Issue 10 (1st October 2019) - Kayani, Babar; Konan, Sujith; Ayuob, Atif; Onochie, Elliot; Al-Jabri, Talal; Haddad, Fares S.
Abstract : Robotic total knee arthroplasty (TKA) improves the accuracy of implant positioning and reduces outliers in achieving the planned limb alignment compared to conventional jig-based TKA. Robotic TKA does not have a learning curve effect for achieving the planned implant positioning. The learning curve for achieving operative times comparable to conventional jig-based TKA is 7–20 robotic TKA cases. Cadaveric studies have shown robotic TKA is associated with reduced iatrogenic injury to the periarticular soft tissue envelope compared to conventional jig-based TKA. Robotic TKA is associated with decreased postoperative pain, enhanced early functional rehabilitation, and decreased time to hospital discharge compared to conventional jig-based TKA. However, there are no differences in medium- to long-term functional outcomes between conventional jig-based TKA and robotic TKA. Limitations of robotic TKA include high installation costs, additional radiation exposure, learning curves for gaining surgical proficiency, and compatibility of the robotic technology with a limited number of implant designs. Further higher quality studies are required to compare differences in conventional TKA versus robotic TKA in relation to long-term functional outcomes, implant survivorship, time to revision surgery, and cost-effectiveness. Cite this article: EFORT Open Rev 2019;4:611-617. DOI: 10.1302/2058-5241.4.190022